IMPLEMENTASI EKSTRAKURIKULER TARI DAN PIDATO DALAM MENINGKATKAN KREATIVITAS SISWA DI SMP IT AR RASYID LIMAU MANIS - Rian Gunawan; Yurmaini; Eka Zuliana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT This study discusses the implementation of Dance and Speech Extracurricular Activities to Enhance Student Creativity at SMP IT Ar Rasyid Limau Manis. The main topics discussed are: How Dance and Speech Extracurricular Activities Work at SMP IT Ar Rasyid Limau Manis, How Dance and Speech Extracurricular Activities Implementation Improves Student Creativity at SMP IT Ar Rasyid Limau Manis, and What are the supporting and inhibiting factors for the implementation of Dance and Speech Extracurricular Activities in Enhancing Student Creativity at SMP IT Ar Rasyid Limau Manis.This study uses qualitative research with descriptive methods and field research. The data for this research was collected from SMP IT Ar Rasyid Limau Manis. The field research findings show the implementation of dance and speech extracurricular activities at SMP IT Ar Rasyid Limau Manis. Dance and speech extracurricular activities are part of the non-academic activities routinely held at SMP IT Ar Rasyid Limau Manis. These activities are supported by the school and are implemented in a structured manner with a schedule, dedicated mentors, and targeted student development. These activities focus not only on technical skills but also serve as a means of character development and self-expression for students. Implementation of Extracurricular Activities in Enhancing Student Creativity. The implementation of dance and speech extracurricular activities has been proven to provide a space for students to express their ideas, talents, and creative thinking skills. In dance activities, creativity is evident through students' ability to explore movement and artistic expression. Meanwhile, in speech activities, students' creativity is evident in their ability to compose scripts, convey ideas, and develop courage in public speaking. Teachers use a varied approach and encourage active participation, making the learning process more lively and supporting the growth of creativity. Factors Supporting and Inhibiting the Implementation of Extracurricular Activities The main supporting factors in implementing this extracurricular activity include school support, the competence of the supervising teacher, student enthusiasm, and the availability of performance venues such as competitions and school events. However, several inhibiting factors also exist, such as limited practice time, inadequate facilities, differences in student ability levels, and a lack of parental support. The school has attempted to overcome these obstacles through flexible time management, a personalized approach to guidance, and active communication with parents.